2020
DOI: 10.21203/rs.3.rs-78780/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acceptance and Risk Perception of COVID-19 Vaccine in Uganda: A Cross Sectional Study in Western Uganda

Abstract: Background: Many countries have drawn their attention on developing Corona virus disease 2019 vaccine however there is less emphasis on whether this vaccine could be accepted in most of these countries. This study aimed to investigate acceptance and risk perception of COVID-19 vaccine in Uganda. Method: A simplified snowball sampling technique was used to select 1067 respondents of 18-70 years in western Uganda using an online questionnaire from July to September 2020. Vaccine acceptability and risk perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
3
8
0
Order By: Relevance
“…The results showed that 54.91% of company workers did not want to be vaccinated against COVID-19 compared to 45.09% of the sample who were willing to receive the COVID-19 vaccine. This vaccination acceptance rate was close to those found in Nigeria [10] and Egypt among health workers [11] and slightly lower than the 50.5% and 53.6% found in Saudi Arabia [12] and Uganda respectively [13]. On the other hand, some studies have found vaccination acceptance rates ranging from 66% to 86% [14][15][16][17][18][19].…”
Section: Fig 2 Reasons For Not Accepting Covid-19 Vaccinationsupporting
confidence: 78%
“…The results showed that 54.91% of company workers did not want to be vaccinated against COVID-19 compared to 45.09% of the sample who were willing to receive the COVID-19 vaccine. This vaccination acceptance rate was close to those found in Nigeria [10] and Egypt among health workers [11] and slightly lower than the 50.5% and 53.6% found in Saudi Arabia [12] and Uganda respectively [13]. On the other hand, some studies have found vaccination acceptance rates ranging from 66% to 86% [14][15][16][17][18][19].…”
Section: Fig 2 Reasons For Not Accepting Covid-19 Vaccinationsupporting
confidence: 78%
“…Third, we found that the lower someone perceived their risk of contracting COVID-19 and/or the vaccine having dangerous side effects, the higher their tendency toward vaccine hesitancy. Vaccine hesitancy cannot lead to being vaccinated if one is concerned about the side effects caused by the vaccine [33]. Attitudes toward the vaccination can be determined depending on the balance between COVID-19 infection, the risk of vaccine's side effects, and attitudes [34].…”
Section: Discussionmentioning
confidence: 99%
“… 11–13 Understanding the severity and risks of the COVID-19 is also associated with public awareness of the dangers and encourages people to be more involved in disease prevention. 12 , 14 , 15 Nevertheless, such factors are not extensively reviewed by the previous studies. The current global acceptance of the COVID-19 vaccines varies from 35% to 98% across countries, indicating that policymakers need to understand the public attitude to assist the large-scale vaccination programs.…”
Section: Introductionmentioning
confidence: 99%